Contract law : rules, theory, and context - Bix, Brian (Cambridge introductions to philosophy and law, 2012)
"Contract law is a category within legal practice (and legal education), though there are many occasions where there are significant overlaps with other categories, or where the borderline is not especially clear. (For example, some commentators have argued that contract law should be seen as a mere sub-category of tort law ; and, in different ways, the boundary lines between contract law and areas like restitution and property are fluid and uncertain much of the time.) Contract law is a category of particular rules and decisions, but (as elsewhere in law) it is a mistake to focus too narrowly on the "facts" of the actual decisions and the "black-letter rules" of treatises. Law is, and likely has always been, a reflective exercise, where there is a natural tendency (among practitioners and observers both) to seek more general principles, to explain and justify past decisions and give guidance for future decisions"-- Provided by publisher